Susceptibility pattern of bacteria isolated from blood cultures of neonates admitted with sepsis at a tertiary care hospital - Munir, Saqib; Hussain, Mudassar; Rasheed, Shahid; Arshad, Salman; Ijaz, Sidra; Qamar, Nadia (Infectious Diseases Journal of Pakistan, 2024)
Background: Neonatal sepsis is one of the leading causes of neonatal mortality rate (NMR) in developing countries like Pakistan, where epidemiologic surveillance of organisms and their antimicrobial sensitivity patterns remains poor. The objective of this study is to identify common organisms implicated in neonatal sepsis and their susceptibility patterns as well as the emergence of antibiotic resistance at a tertiary care hospital. Material and Methods: This Retrospective descriptive study, Blood culture reports of neonates admitted to the Nursery of Allama Iqbal Memorial Teaching Hospital (Khawaja Muhammad Safdar Medical College) with suspected sepsis from January 2020 to December 2022 were taken. Results: Blood culture reports were positive in 303 (12.8%) out of 2368 neonates. The proportion of gram-negative and gram-positive micro-organisms were 278 (91.7%) and 25 (8.3%) respectively. Acinetobacter baumannii was the most predominant microorganism isolated (32.3%), followed by E coli (21.4%) and Citrobacter freundii (13.5%). Among the gram-negative microorganisms high level of resistance was seen with first-line agents, such as ampicillin (97.3%), third generation cephalosporins i:e cefotaxime (89.8%), while the majority of these organisms were sensitive to carbapenems (56.0%) and cefoperazone-sulbactam (53%). Methicillin resistant Staphylococcus aureus rate was 47.6% and no resistance to vancomycin and linezolid was detected. Conclusion: This study shows the emergence of unusual gram-negative microorganisms causing neonatal sepsis and a high level of resistance to first-line empirical antibiotic therapy. This highlights the urgent need for the implementation of effective infections control program and antibiotics stewardship in neonatal ICU. Keywords: Antibiotic susceptibility, Blood culture, Neonatal sepsis